Activation of growth and development of sugar beet at microstages 00-09 with application of nanoscale fertilizer elements - Н. В. Новицька; С. М. Каленська; О. І. Присяжнюк; В. В. Мельниченко (Plant Varieties Studying and Protection)
Purpose. Finding ways to activate the germination of sugar beet seeds, obtaining even and synchronous sprouts when applying fertilizer compositions with nanoscale elements.